NFATc1 is a tumor suppressor in hepatocellular carcinoma and induces tumor cell apoptosis by activating the FasL‐mediated extrinsic signaling pathway. (7th August 2018) - Xu, Sanrong; Shu, Penghao; Zou, Song; Shen, Xiaofeng; Qu, Yuanqian; Zhang, Yong; Sun, Kang; Zhang, Jin
Abstract: Nuclear factor of activated T cells (NFAT) is a family of transcription factors that have important functions in many tumors. However, the expression level and functional role of NFAT in hepatocellular carcinoma (HCC) remain unclear. In this study, we showed that NFATc1 expression was decreased in both HCC tissues and cell lines. Low expression of NFATc1 was correlated with larger tumor size, advanced tumor‐node‐metastasis (TNM) stage, high serum AFP level, and liver cirrhosis. Furthermore, patients with low NFATc1 expression exhibited poor prognosis. Ectopic expression of NFATc1 in HCC cells inhibited proliferation and colony formation, leading to G1 arrest and induction of apoptosis. In addition, we demonstrated that NFATc1 increased Fas ligand (FasL) expression by directly binding to its promoter and activated the extrinsic apoptotic pathway. NFATc1 and FasL expression patterns and their prognostic value for patients with HCC were also evaluated in TCGA Liver Hepatocellular Carcinoma database. Knock‐down of FasL expression by siRNA in HCC cell lines abolished NFATc1's antiproliferative and pro‐apoptotic effects. In conclusion, NFATc1 is frequently inactivated in HCC and functions as a tumor suppressor in liver carcinogenesis. Ectopic expression of NFATc1 in HCC cells induces apoptosis by activating the FasL‐mediated extrinsic signaling pathway. Abstract : Nuclear factor of activated T‐cell cytoplasmic 1 expression is silenced in HCC. Ectopic expression of NFATc1 induced FasL expression through direct binding to its promoter and induction of apoptosis signaling, including caspase 8 and caspase 3 activation, eventually leading to apoptosis.